Dampak Ketidakmerataan Pembayaran Pajak Terhadap Distribusi Pendapatan dan Keadilan Sosial - Patricia, Viane; Putri, Sanny Nuyessy; Rasji, Rasji (Peneliti.net, 2024)
Inequality in tax payments is a complex issue that has a significant impact on income distribution and social justice in Indonesia. In the context of this case study qualitative research, secondary data from official sources such as the Directorate General of Taxes, the Central Statistics Agency, and government reports are used to analyze the impact of unequal tax payments. This study shows that unequal tax payments can trigger increasing social and political inequality in society. The impact extends to the development and public services sectors, with a lack of funding available to support welfare programs and necessary infrastructure. Apart from that, unequal tax payments also contribute to greater income inequality in society. However, the Indonesian government has responded to this issue with various policies, including the Economic Equalization Policy (KPE), healthy fiscal policies through the Budget, and the Tax Amnesty program. Taxes are considered a tool for income redistribution, with progressive taxation on individuals with higher incomes. Awareness of the importance of paying taxes fairly and tax policies that support a more equal distribution of income are important steps towards a more just and sustainable society in Indonesia. Collaboration between government, the private sector and society is needed to overcome this problem and achieve better social welfare and maintain social and political stability.